High School Track Choice and Financial Constraints : Evidence from Urban Mexico - Avitabile, Ciro (World Bank, Washington, DC, 2015)
Parents and students from different socioeconomic backgrounds value differently school characteristics, but the reasons behind this preference heterogeneity are not well understood. In the context of the centralized school assignment system in Mexico City, this study analyzes how a large household income shock affects choices over high school tracks exploiting the discontinuity in the assignment of the welfare program Oportunidades. The income shock significantly increases the probability of choosing the vocational track vis-a-vis the other more academic-oriented tracks. The findings suggest that the transfer relaxes the financial constraints that prevent relatively low-ability students from choosing the schooling option with higher labor market returns.